2005
DOI: 10.1007/s10582-006-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous edge E × B sheared flow development studies in the TJ-II stellarator

Abstract: The influence of plasma density and edge gradients in the development of perpendicular sheared flow has been investigated in the plasma edge region of the TJ-II stellarator. It has been experimentally observed that the generation of spontaneous perpendicular sheared flow (i.e. the naturally occurring shear layer) requires a minimum plasma density or gradient. It has been found that there is a coupling between the onset of sheared flow development and an increase in the level of plasma edge turbulence; once she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The contribution from each parameter to the critical line-density is obtained subtracting the contribution from the other parameters. These results partially confirm preliminary results obtained using Langmuir probes and reported in [13,14]. The opposite exponential dependences as compared with the energy confinement time may reflect the influence of the radial electric field profile on the confinement.…”
Section: Resultssupporting
confidence: 91%
“…The contribution from each parameter to the critical line-density is obtained subtracting the contribution from the other parameters. These results partially confirm preliminary results obtained using Langmuir probes and reported in [13,14]. The opposite exponential dependences as compared with the energy confinement time may reflect the influence of the radial electric field profile on the confinement.…”
Section: Resultssupporting
confidence: 91%
“…In plasmas with densities below the critical value, the plasma potential increases from the plasma edge to the centre, and therefore the radial electric field is positive in the entire plasma column. At higher densities the radial electric field is negative at the periphery and remains positive at the plasma core [20]. These HIBP measurements indicate that the inversion in the perpendicular rotation velocity that we measure using the reflectometer is dominated by the radial electric field.…”
Section: Resultssupporting
confidence: 49%
“…Transition to an improved confinement regime has been observed in TJ-II for some ECRH plasma conditions [19], [20]. In agreement with this result, it has been shown that the development of sheared flows at the plasma edge of the TJ-II requires a critical value of plasma density or density gradient that depends on global plasma parameters [9], [10], [21], [22]. Radial profiles of measured plasma edge parameters are strongly modified as plasma density increases: the gradient of the ion saturation current increases and the floating potential becomes more negative at the plasma edge.…”
Section: Confinement Transitions In Tj-ii Ecrh Plasmasmentioning
confidence: 59%